2009
DOI: 10.1186/1477-7517-6-21
|View full text |Cite
|
Sign up to set email alerts
|

Needle and syringe sharing among Iranian drug injectors

Abstract: Objective: The role of needle and syringe sharing behavior of injection drug users (IDUs) in spreading of blood-borne infections -specially HIV/AIDS -is well known. However, very little is known in this regard from Iran. The aim of our study was to determine the prevalence and associates of needle and syringe sharing among Iranian IDUs. Methods:In a secondary analysis of a sample of drug dependents who were sampled from medical centers, prisons and streets of the capitals of 29 provinces in the Iran in 2007, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 36 publications
1
34
1
1
Order By: Relevance
“…With respect to recruitment site, in two studies, there was no difference in mean AFI between PWID recruited from community, treatment centers, and prisons (Narenjiha, et al, 2009; Narenjiha, et al, 2005), however, another study, conducted in the same city, found the AFI was considerably higher in PWID recruited from treatment centers versus those from community and Drop in Centers (DICs) (30.3. vs 24.7, p <0.001) (Rahimi-Movaghar, et al, 2008). While one study reported no difference in mean AFI between those who had shared needles and syringes and those who had not (Rafiey et al, 2009), another study (Mohammad, et al, 2008) reported a significant difference in mean AFI (shared 20.3 vs. not shared 26.4, p <0.001). Finally, only one study reported no significant difference in AFI for PWID by HCV sero-status (Zamani, Radfar, et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to recruitment site, in two studies, there was no difference in mean AFI between PWID recruited from community, treatment centers, and prisons (Narenjiha, et al, 2009; Narenjiha, et al, 2005), however, another study, conducted in the same city, found the AFI was considerably higher in PWID recruited from treatment centers versus those from community and Drop in Centers (DICs) (30.3. vs 24.7, p <0.001) (Rahimi-Movaghar, et al, 2008). While one study reported no difference in mean AFI between those who had shared needles and syringes and those who had not (Rafiey et al, 2009), another study (Mohammad, et al, 2008) reported a significant difference in mean AFI (shared 20.3 vs. not shared 26.4, p <0.001). Finally, only one study reported no significant difference in AFI for PWID by HCV sero-status (Zamani, Radfar, et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the heterogeneity of studies and reported outcomes, we did not calculate a summary mean for the length of time to transition. Four studies found that, on average, drug users were using drugs for six to seven years before their first injection (Amin-Esmaeili, et al, in Print; Rafiey, et al, 2009; Razzaghi & Rahimi-Movaghar, 2005; Samimi-Rad et al, 2012). Two studies reported that 50% of subjects had initiated injection within four years of starting drug use (Rahimi-Movaghar, et al, 2008; Vazirian, et al, 2006), and one study reported a wider range of between five to 15 years after initiation of drug use.…”
Section: Resultsmentioning
confidence: 99%
“…This study was conducted under the financial aid of the Drugs Control Headquarters. Some other reports have been extracted from this database (6, 2327). …”
Section: Methodsmentioning
confidence: 99%
“…An international report indicates that the number of people who inject drugs (PWID) is approximately 180,000 in Iran (1). A rapid situation assessment (RSA) study conducted by drug control headquarter (DCHQ) showed that 18.1% out of 1.2 million drug users reported injection as their main route of drug administration; 26.5% of them had at least one injection during last year and 6.7% of them reported using needles, syringes and injecting equipment used by other drug users (3). People who inject drugs are the most HIV-infected population in Iran and contribute to approximately 67% of all identified cases of HIV infection in the country (4).…”
Section: Introductionmentioning
confidence: 99%